Patterns and predictors of trajectories for subjective quality of life in patients with early psychosis: Three-year follow-up of the randomized controlled trial on extended early intervention. (October 2021) - Kam, Candice Tze Kwan; Chang, Wing Chung; Kwong, Vivian Wing Yan; Lau, Emily Sin Ki; Chan, Gloria Hoi Kei; Jim, Olivia Tsz Ting; Hui, Christy Lai Ming; Chan, Sherry Kit Wa; Lee, Edwin Ho Ming; Chen, Eric Yu Hai
Objective: Subjective quality of life is an important outcome of psychotic disorders. However, longitudinal course of subjective quality of life in the early illness stage is under-studied. We aimed to investigate the patterns and baseline predictors of subjective quality of life trajectories over 3 years in early psychosis patients, utilizing growth mixing modeling analysis, in the context of a 3-year follow-up of a randomized controlled trial comparing 1-year extension of early intervention with step-down psychiatric care for first-episode psychosis. Method: One hundred sixty Chinese patients were recruited from specialized early intervention program for first-episode psychosis in Hong Kong after they had completed this 2-year early intervention service, and underwent 1-year randomized controlled trial as well as 2-year post–randomized controlled trial follow-up (i.e. 3-year follow-up). Assessments on premorbid adjustment, onset profile, psychopathology, functioning and treatment characteristics were conducted. Individual class membership of subjective quality of life trajectory derived from growth mixing modeling was based on the 36-Item Short Form Health Survey mental component summary scores measured at four different time-points (baseline, 1, 2 and 3 years) among 142 participants across 3-year follow-up. Results: Three distinct subjective quality of life trajectories were identified including higher-improving (68.3%, n  = 97), lower-stable (24.6%, n  = 35) and deteriorating (7%, n  = 10) trajectories. Age of onset; duration of untreated psychosis; depressive, positive and negative symptoms; and intervention condition were significantly different between good (higher-improving trajectory) and poor (combined lower-stable and deteriorating trajectories) trajectory groups. Multiple regression analysis revealed that younger age of onset, more severe depression and receipt of step-down care independently predicted poor subjective quality of life trajectory. Conclusion: Approximately one-third of patients displayed poor subjective quality of life trajectory in the early phase of psychotic illness. Our results affirm depression as a critical determinant of prospective subjective quality of life and underscores positive effect of extended early intervention on sustained subjective quality of life improvement. Further longitudinal research is warranted to facilitate better characterization of subjective quality of life course patterns and development of targeted intervention to optimize subjective quality of life in patients with early psychosis.